2017
DOI: 10.7448/ias.20.5.21644
|View full text |Cite
|
Sign up to set email alerts
|

Implications of differentiated care for successful ART scale‐up in a concentrated HIV epidemic in Yangon, Myanmar

Abstract: Introduction: National AIDS Programme in Myanmar has made significant progress in scaling up antiretroviral treatment (ART) services and recognizes the importance of differentiated care for people living with HIV. Indeed, long centred around the hospital and reliant on physicians, the country’s HIV response is undergoing a process of successful decentralization with HIV care increasingly being integrated into other health services as part of a systematic effort to expand access to HIV treatment. This study des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…Further research is needed to evaluate the potential for scale-up of the identified innovations in service delivery models. Our findings add to the mounting calls for implementation of differentiated care models for ART service delivery in resource-limited settings [ 7 , 49 , 50 ]. In a study evaluating the implementation of a health systems strengthening intervention in three districts in Zambia, Mutale and colleagues [ 51 ] found that the shortage of trained health workers negatively affected service delivery and undermined outcomes of implementing a complex health system intervention.…”
Section: Discussionsupporting
confidence: 54%
“…Further research is needed to evaluate the potential for scale-up of the identified innovations in service delivery models. Our findings add to the mounting calls for implementation of differentiated care models for ART service delivery in resource-limited settings [ 7 , 49 , 50 ]. In a study evaluating the implementation of a health systems strengthening intervention in three districts in Zambia, Mutale and colleagues [ 51 ] found that the shortage of trained health workers negatively affected service delivery and undermined outcomes of implementing a complex health system intervention.…”
Section: Discussionsupporting
confidence: 54%
“…Two articles by MSF highlight examples of differentiated ART delivery outside of sub-Saharan Africa. Mesic et al report on the client and health system implications of an individual facility-based model for stable clients in Yangon, Myanmar [ 33 ]. Their findings present novel evidence of the success of differentiated ART delivery for stable clients in a concentrated HIV epidemic.…”
Section: Beyond the Context Of Sub-saharan Africa And High-prevalencementioning
confidence: 99%
“…The differentiated care model is a well-known approach for care for people living with HIV (PLHIV). This model has been successfully used to categorise stable versus unstable PLHIV in order to provide differentiated care [13]. In India, PLHIV with TB are: screened regularly using a four symptom screening, a priority group for diagnosis by Cartridge based Nucleic Acid Ampli cation Test (CB-NAAT), and recommended for early initiation of both anti-tuberculosis treatment (ATT) as well as early initiation of anti-retroviral treatment (ART).…”
Section: Discussionmentioning
confidence: 99%